Acoustic Pressure Radiated by a Circular Membrane Into the Quarter-Space - RDZANEK, Wojciech P.; SZEMELA, Krzysztof; PIECZONKA, Dawid (Archives of Acoustics, 2011)
The Neumann boundary value problem for the Helmholtz equation within thequarter-space has been considered in this paper. The Green function has been usedto find the acoustic pressure amplitude as the approximation valid within the Fraunhoffer’szone for some time-harmonic steady state processes. The low fluid loadinghas been assumed and the acoustic attenuation has been neglected. It has also beenassumed that the vibration velocity of the acoustic particles is small as comparedwith the sound velocity in the gaseous medium.